Effective temperature of ionizing stars in extragalactic H II regions: II. Nebular parameter relationships based on CALIFA data - Zinchenko, Igor A. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We calculate the effective temperature (Teff) of ionizing star(s), the oxygen abundance of the gas phase $(\rm O/H)$, and the ionization parameter U